THE INFLUENCE OF GADGET USE ON LANGUAGE DEVELOPMENT IN CHILDREN AGED 4-5 YEARS - Sahrul, Sahrul; Arumsari, Diah Ayu; Rochmawan, Muhammad Rizky; Pilar Ratri, Mayla Faiza; Fatmawati, Sephia Putri; Khasanah, Hikmah Nur; Marfu'ah, Sri; Irmaya, Irmaya (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
The provision of gadgets to children at this age can affect language development; by frequently using gadgets, children will become accustomed to practicing speech or communication. The purpose of this research is to understand the development of children's language when using gadgets. with a research design that involves developing instruments and conducting observations in the classroom by checking items on the statement list Statistical data analysis was conducted by testing the instrument with four expert raters in their field, followed by a validity test using Aiken’s V formula. Based on the results of the statistical test conducted, there is an influence of the gadget variable (X) on language development of 65.8%, while 34.2% can be influenced by additional variables that have not yet been studied. To test the significance of the regression line equation, the p-value in the General Model Test column can be used. A p-value less than (<) 0.05 indicates that the regression line equation is significant. This indicates that the regression line equation can be relied upon to estimate the variable of device usage in the language development of 4-5 year old children.